Strategi Pemasaran 4P pada Home Industry Winwin Bakery dalam Meningkatkan Promosi Penjualan di Era Milenial (Study Kasus di Kecamatan Tilamuta) - Lilis Lihawa; Mahludin H. Baruwadi; Larasati Sukmadewi Wibowo (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
This study aims to identify internal and external factors in the marketing of business products that influence the development of the Winwin Bakery home industry in Tilamuta District and to compile the application of marketing strategies for bakery products to the Winwin Bakery home industry on social media in the millennial era. This research uses case study research that produces descriptive data with data analysis techniques, namely SWOT analysis with ten informants—collecting data by conducting observations, interviews, and documentation. The types and sources of data are primary data and secondary data. The research results show that the factors contained in the Winwin Bakery business are internal factors (strengths and weaknesses). External factors (opportunities and threats), the opportunity factor in the Winwin Bakery business is that the company has met the requirements for an MUI halal certificate permit. In contrast, the threat factor is the existence of a branch of similar bakery industry. Implementing marketing strategies through social media such as Facebook and Instagram in the millennial era will make it easier for consumers to find out the latest menus and promotions, to be closer to customers and consumers easily find out the products or promotions currently in effect at Winwin Bakery.